Assessing the Impact of Simulation-Based Learning on Student Satisfaction and Self-Confidence in Critical Care Medicine - Mohammed Ageel (Critical Care Research and Practice)
Conclusion: The SBL intervention was effective in enhancing student satisfaction and self-confidence in critical care medicine. The strong correlation between satisfaction and self-confidence highlights the importance of well-designed SBL programs in preparing medical students for clinical practice in critical care settings.